Pengembangan Marketing UMKM Jamu Tradisional Di Desa Pangkatrejo Kecamatan Sugio Kabupaten Lamongan Dengan Metode Rebranding - Ulfa Khoiriyah; Andika Dafa Penta Pratama; Hadad Alwi; Bayu Malikhul Askhar; Tri Winarsih; Ronalmanto Ronalmanto; Muhammad David (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are essential for driving economic growth and creating jobs, especially within the traditional jamu industry. In Pangkatrejo Village, jamu MSMEs encounter difficulties such as a lack of branding knowledge and inefficient marketing strategies. Given the growing interest in natural products after the Covid-19 pandemic, jamu has the opportunity to emerge as a prominent product. This activity involves a support program for traditional jamu MSMEs in Pangkatrejo Village, concentrating on rebranding efforts that involve packaging design, modernizing bottles, and developing social media presence. The goal is to improve the visibility and competitiveness of jamu products, as well as to expand the market and strengthen the local economy.